Rola sądów administracyjnych w nowozelandzkim systemie prawnym - Siekiera, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article describes administrative judiciary in New Zealand, as well as its significant role in the whole legal system of the country. The development of administrative tribunals in many countries may differ, as it is associated with the constantly increasing power of any state bodies. Administrative competences do gradually rise due to the complexity of New Zealand society, but also as a response to non-compliance with social justice. In New Zealand, state carries out the functions which until recently were, or in certain countries are still, in private hands. In addition, the New Zealand administrative law system includes such institutions as the Court of Copyright, the Office of Pharmacy or the College of Appeal Land.
Keywords: New Zealand judiciary; New Zealand law; New Zealand legal system; administrative tribunals; administration; New Zealand administration; New Zealand